1997
DOI: 10.1007/s001340050495
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam versus propofol for long-term sedation in the ICU: a randomized prospective comparison

Abstract: Both drugs afforded reliable, safe, and controllable long-term sedation in ICU patients and rapid weaning from mechanical ventilation. Midazolam depressed respiration, allowed better maintenance of sedation, and yielded complete amnesia at a lower cost, while propofol caused more cardiovascular depression during induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 28 publications
4
62
0
Order By: Relevance
“…Although both midazolam and propofol have a quick onset of sedative effect, several investigations support the notion that the time between drug discontinuation and awakening is appreciably shorter when propofol is used (7,8,21,22). In fact, in our study, comparison of sedation duration during the first 3 days of mechanical ventilation showed that midazolam infusions were continued for a significantly shorter duration than propofol infusions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although both midazolam and propofol have a quick onset of sedative effect, several investigations support the notion that the time between drug discontinuation and awakening is appreciably shorter when propofol is used (7,8,21,22). In fact, in our study, comparison of sedation duration during the first 3 days of mechanical ventilation showed that midazolam infusions were continued for a significantly shorter duration than propofol infusions.…”
Section: Discussionsupporting
confidence: 65%
“…Since none of these drugs have analgesic properties, an opiate drug is often administered concurrently. Although comparative studies of propofol vs. midazolam have addressed safety, duration of mechanical ventilation, level of sedation, costs, and ease of use, no investigation has looked for differences in sedation requirements associated with PH (7,8).…”
mentioning
confidence: 98%
“…Tbe PAD guidelines subsequently offered a weak recommendation favoring tbe use of IV nonbenzodiazepine sedatives (eitber dexmedetomidine or propofol) over benzodiazepine sedatives (eitber lorazepam or midazolam) in mecbanically ventilated adults. Tbis recommendation was based on an evaluation of 13 studies publisbed between 1997 and 2010 tbat compared IV benzodiazepine sedative regimens witb eitber IV dexmedetomidine or propofol (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Figure 1 shows the distribution of morphine equivalent doses in mg/kg/day in 26 studies. The median dose was 0.7 mg/kg/day or about 49 mg/day for a patient weighing 70 kg (Sun et al 1992;Carrasco et al 1993;Sun and Weissman 1994;Ronan et al 1995;Kress et al 1996;Barrientos-Vega et al 1997;Devlin et al 1997;McLeod et al 1997;Watling et al 1997;Weinbroum et al 1997;Cammarano et al 1998; Sanchez-Izquierdo-Riera et al Brook et al 1999;Devlin et al 1999;Swart et al 1999;Fraser et al 2000;Kress et al 2000;Brandl et al 2001;Ely et al 2001;Payen et al 2001;Ely et al 2003;De Jonghe et al 2005;Kahn et al 2005;Carson et al 2006;Wolthuis et al 2007;Girard et al 2008). …”
Section: Opioid Use In the Icumentioning
confidence: 97%